2022
DOI: 10.1007/s10834-022-09859-8
|View full text |Cite
|
Sign up to set email alerts
|

What Matters When Examining Attitudes of Economic Abuse? Gender and Student Status as Predictors of Blaming, Minimizing, and Excusing Economic Abuse

Abstract: Extensive research has been conducted regarding attitudes toward various types and patterns of violence against intimate partners, but there is a lack of research on attitudes toward economic abuse in general. In the current study, we examined attitudes toward economic abuse by examining how participants blamed the victim, minimized the economic abuse, and excused the perpetrator in hypothetical scenarios. We also examined two characteristics of participants: binary gender differences (i.e., woman, man) and di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 73 publications
1
2
0
Order By: Relevance
“…This finding is consistent with previous findings in which women had higher levels of empathy toward victims of abuse and therefore blamed the victim less than men did (Laso & Rodríguez-Diaz, 2022). Researchers found that men were more likely to blame the victim and minimize economic abuse in a study comparing differences in attitudes of economic abuse with male and female participants (Green et al, 2022). These results suggest that once a man becomes a victim of IPV, others, such as his male family members or friends, may blame or minimize the seriousness of the IPV, making male victims very vulnerable among IPV victims.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This finding is consistent with previous findings in which women had higher levels of empathy toward victims of abuse and therefore blamed the victim less than men did (Laso & Rodríguez-Diaz, 2022). Researchers found that men were more likely to blame the victim and minimize economic abuse in a study comparing differences in attitudes of economic abuse with male and female participants (Green et al, 2022). These results suggest that once a man becomes a victim of IPV, others, such as his male family members or friends, may blame or minimize the seriousness of the IPV, making male victims very vulnerable among IPV victims.…”
Section: Discussionsupporting
confidence: 91%
“…Our findings are similar to findings from physical and emotional IPV or stalking perception studies. Respondents perceived different types of IPV in accordance with stereotypical gender roles (Green et al, 2022;Hammock et al, 2017). Given the increased prevalence of female-to-male IPV and the fact that more women than The results also showed that there was a significant main effect of participants' gender on both blaming and minimization.…”
Section: Discussionmentioning
confidence: 85%
“…Economic abuse is a global social problem that cuts across socioeconomic and demographic groups (Green et al, 2022). Economic abuse refers to coercive intents to control or prevent partners from "acquiring," "maintaining," or "using" resources, which may affect partners' economic security and self-sufficiency (Adams et al, 2008).…”
Section: Introductionmentioning
confidence: 99%